Community-based dark tourism development strategy in the disaster-prone area of Mount Semeru, East Java - Arinta, Dicky; Sumarmi; Suprianto, Agung; Windayu, Cinde Ririh; Triningsih, Luly; Okafor, Christian Emeka (Universitas Negeri Malang, 2025)
Pronojiwo District has a geological uniqueness because some areas are close to the Mount Semeru area. The history of the eruption of Mount Semeru on December 4, 2021, which had a wide impact on society and the environment. This study aims to identify the potential and formulate a strategy for developing dark tourism in the slopes of Mount Semeru, especially in Pronojiwo District, Lumajang Regency. The research method uses a qualitative and quantitative descriptive approach to understand the potential, challenges, and management models for dark tourism on the slopes of Mount Semeru. The results of the study show that the potential for dark tourism was identified through spatial analysis of affected locations and mapping of tourist attractions such as Tumpak Sewu, Kapas Biru, Kali Kebo, Sarkawi, and Sumberurip which are within a radius of <5 km from the center of volcanic activity. In addition, Pronojiwo District is in quadrant I (Strength-Opportunity), indicating high potential for growth-based development. The development strategy focuses on two main aspects: improving destination management (attraction, promotion, institutions) and strengthening human resources (training, disaster literacy, and certification of tourism actors). This study shows that community-based dark tourism in the Semeru area can be a model for developing reflective and educational tourism in Indonesia, while also contributing to strengthening the local economy, disaster awareness, and community resilience.